IAP Guideline on Practicing Safely During COVID-19 Era: Clinics and Small Establishments - Basavaraja, G. V.; Chandrasekar, Supraja; Bansal, Arun; Gupta, Dhiren; Parekh, Bakul Jayant; Kamath, S. S.; Desai, Snehal; Nagar, Pritesh; Shah, Nitin; Bhadra, Atanu; Chitkara, A. J. (Indian pediatrics, 2021)
Justification The unprecedented COVID-19 pandemic has had a formidable impact on Indian health care. With no sight of its end as yet, various establishments including the smaller clinics and nursing homes are restarting full operations. Hence, there is the need for recommendations to allow safe practice ensuring the safety of both the heath care worker (HCW) and patients. Process Indian Academy of Pediatrics organized an online meeting of subject experts on 27 July, 2020. A committee was formed comprising of pediatricians, pediatric and neonatal intensivists, and hospital administrators. The committee held deliberations (online and via emails) and a final consensus was reached by November, 2020. Objectives To develop recommendations to provide a safe and practical healthcare facility at clinics and small establishments during COVID times. Recommendations The key recommendation to practise safely in this setting are enumerated. Firstly, organizing the out-patient department (OPD). Secondly, appropriate personal protective equipment (PPE) to provide protection to the individual. Thirdly, decontamination/disinfection of various common surfaces and equipment to prevent transmission of infection from fomites. Next, maintaining the heating ventilation and air conditioning (HVAC) to provide a stress-free, comfortable, and safe environment for patients and HCWs. Finally, steps to effectively manage COVID-19 exposures in a non-COVID-19 facility. All these measures will ensure safe practice during these unprecedent times in clinics and smaller establishments.